The lanthipeptides of Bacillus methylotrophicus and their association with genomic islands - Dias, L.
tBacillus methylotrophicus strains are known for their potential as plant-growth promoters and as micro-bial pesticides that effectively control plant diseases caused by bacteria and fungi. Over the past few years,a wide diversity of their secondary metabolites has been extensively characterized. Among these are theRiPPs lanthipeptides, which are an important and growing group of notable compounds. The increasinginterest in B. methylotrophicus species, accompanied by the development of high throughput sequenc-ing techniques, has resulted in a substantial number of full genomes being available. Here, an in silicoanalysis was performed on these genomes in order to survey the presence of lanthipeptide biosyntheticclusters. It was found that the pan genome of B. methylotrophicus only encoded the biosynthesis of mer-sacidin and amylolysin, which are lanthipeptides with antibacterial activity. However, the amylolysingene cluster identified was comprised of more genetic elements than those previously described, and ithad certain features of two-peptide lantibiotics. Additionally, it was also established that the associationof lanthipeptides with genomic islands (GIs) was not confined to mersacidin. This was also found forthe amylolysin cluster as well as other class I and class II lanthipeptides, supporting the idea that theirproduction is probably related to functional adaptation.